Control Networks in Cameroonian SMEs: Influence of Selection Criteria on Performance Partners - Nana, Tyeri Basilide Tcheubeu; Ndzogoue, Alain Bernard; Kamdem, David (Prabandhan: Indian Journal of Management, 2015)
The objectives of the present study are to understand and describe the criteria for selecting partners in networks of SMEs, whether these criteria can explain the performance of SMEs. From an observation of 54 Cameroonian SMEs in the manufacturing and logistics sectors, it appears that these SMEs (while selecting partners) took into account some very important criteria such as: price, quality, past relationships ; as a significant criteria, production capacity, reputation, and technical ability were taken into account. From literature, we know that when partners are selected using criteria developed properly, it has an influence on business performance, but we found that despite the inclusion of these criteria, it does not alter the opportunism of actors, which remains in the background selection, and therefore, does not explain performance.